Lenz-Bilder Bildlichkeit in Büchners Erzählung und ihre Rezeption in der bildenden Kunst. - Neuhuber, Christian (2009)
Since the beginning of reception, Büchner's epoch-making narrative Lenz was praised for its iconic quality, for the suggestive verbal mediacy of visual experience and the evocation of mental pictures. But so far research has paid no attention to the fact that this specific interrelation of language and image also strongly influenced the reception of the narrative in the fine arts. For the first time, this study analyses the complex relations between text and image in Lenz and its reception comprehensively, i.e. in consideration of the trias of literary communication: author, work and (artistic) reader. Firstly it is shown how the text-image-relations form the aesthetic fundament of the narrative as means of composition, but also as thematic, metareflexive element. Subsequently the different forms of imagery are analysed, which are generated in this way. The final part of the study presents illustrations based on Lenz and confronts them with the text. More than 700 pictures from 47 artists could be found, e.g. the expressive self-portraits of Walter Gramatté, Toyen's surrealistic compositions, the 'degenerative' etchings of Susanne Theumer or Thomas Kohl's landscape-representations.